The adequacy of the malay reservation land enactment in protecting the proprietorship of the malay over malay reservation land in West Malaysia / Ima Mastura Ramly...[et al.] - Ramly, Ima Mastura; Ramie, Najwa; Mohd Raya, Nurul Ikrimah; Basri, Zatil Farhah; Abd Wahab, Noor Fateha (2011)
The Malay Reservation Land is a special category of land within the boundary of a state, which can only be owned and dealt with by Malays, being the natives of the state. However, this restriction does not in any way protect or safeguard MRL from depletion through any deals with the non-Malays and the convenient machinery of acquisition by a State or Federal Government. This research entails the problem hidden beyond the well illustrated legal system. The study on various native land law over other countries also been conducted. Interviews are conducted to the government bodies and non-governmental organizations. The results of the interviews are analyses to seek on the major differences of these laws. Accordingly, these analyses are recorded and conclusions are made. Reports on the interviews are made. The reports shows there are certainly some areas in the local laws that need amendments. Therefore, amendments in terms of sufficiency of the punishment, protection and enforcement of the local law are necessary.